Worldbuilding in Tolkien’s Middle-earth and Beyond (KULT_online, 2020)
The field of worldbuilding in literary studies is experiencing a revitalization and it is therefore unsurprising that interest in Tolkien’s Middle-earth is renewed. Many aspects of Tolkien’s world have been analyzed and discussed, but it remains a relevant topic for both specific questions concerning Tolkien’s world and general questions concerning worldbuilding in literature. Sub-creating Arda, edited by Dimitra Fimi and Thomas Honegger, makes a valuable contribution that expands on both theoretical areas, applies theories of worldbuilding to Middle-earth, and draws interesting parallels to other fictional worlds. Because the field of worldbuilding is incredibly rich, Sub-creating Arda is not exhaustive, but nevertheless makes significant contributions to contemporary academic problematizations of the field and will undoubtedly inspire new arguments and new approaches within the field of worldbuilding.